2009
DOI: 10.1158/0008-5472.can-08-2920
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-205 Regulates HER3 in Human Breast Cancer

Abstract: An increasing amount of experimental evidence shows that microRNAs can have a causal role in breast cancer tumorigenesis as a novel class of oncogenes or tumor suppressor genes, depending on the targets they regulate. HER2 overexpression is a hallmark of a particularly aggressive subset of breast tumors, and its activation is strictly dependent on the trans-interaction with other members of HER family; in particular, the activation of the PI3K/Akt survival pathway, so critically important in tumorigenesis, is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
228
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(243 citation statements)
references
References 20 publications
11
228
0
4
Order By: Relevance
“…Its functions in cancer appear to be tissue type specific. MiR-205 expression level is reportedly upregulated in human samples of lung cancer, 69 bladder cancer, 70 and endometrioid adenocarcinoma, 71 and downregulated in breast cancer, [72][73][74] prostate cancer, 75 and melanoma. 76 It has been reported that in a cohort of early breast cancer patients, decreased miR-205 is associated with worse disease-free interval and overall survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its functions in cancer appear to be tissue type specific. MiR-205 expression level is reportedly upregulated in human samples of lung cancer, 69 bladder cancer, 70 and endometrioid adenocarcinoma, 71 and downregulated in breast cancer, [72][73][74] prostate cancer, 75 and melanoma. 76 It has been reported that in a cohort of early breast cancer patients, decreased miR-205 is associated with worse disease-free interval and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…26 Identified direct targets of miR-205 in breast cancer include VEGF-A, a key regulator of angiogenesis and tumor metastasis, 72 E2F1, LAMC1, 79 and HER3. 72,73 Heterodimerization of HER2-HER3 leads to the activation of PI3K/Akt survival pathway, critical for HER2-mediated tumorigenesis. It was found that enforced expression of miR-205 in cultured breast cancer cells increases the responsiveness to EGFR inhibitor Gefitinib and EGFR/HER2 inhibitor Lapatinib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ichikawa et al also found that miR-26a and miR-30b mediate the effects of trastuzumab. 79,80 Furthermore, Iorio et al 81 demonstrated that miR-205, which targets HER3 and impairs the downstream Akt-mediated survival pathway, not only has an oncosuppressive role in breast cancer, but also increases its responsiveness to lapatinib and gefitinib.…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%
“…9,10 microRNA205 (miR-205) has previously been cited as targeting HER3, SHIP2, VEGF-A, MED1, SIP1 and ZEB1 for repression. [11][12][13][14][15] In addition, miR-205 has been shown to activate IL24 and IL32 by targeting sites on their promoters. 16 In PCa, miR-205 exerts a tumorsuppressive effect by counteracting the epithelial-to-mesenchymal transition and reducing cell migration/invasion, in part through the down-regulation of protein kinase C epsilon.…”
Section: Introductionmentioning
confidence: 99%